2018
DOI: 10.1002/brb3.1124
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen in paroxysmal sympathetic hyperactivity: Impact on oral treatment

Abstract: IntroductionIntrathecal baclofen (ITB) is a commonly used treatment in severe spasticity. The main objective of this study was to assess the impact of ITB on reduction or withdrawal of oral drugs in patients with paroxysmal sympathetic hyperactivity (PSH) after severe traumatic brain injury.MethodsWe retrospectively evaluated 20 patients with PSH due to severe traumatic brain injury who were treated with ITB in a primary care and referral center of neurology. Rates of and time until complete withdrawal or poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The same question for ITB revealed that ITB is proposed later than BoNT in clinical practice, with the respondents recommending waiting at least 4–6 months (22/77; 28.6%) or more than 6 months (20/77; 26.0%), depending on the cause of spasticity, before treating patients with ITB. This is clearly inappropriate if patients are losing range, particularly in the context of dysautonomia following brain injury, where ITB has been shown to be beneficial ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same question for ITB revealed that ITB is proposed later than BoNT in clinical practice, with the respondents recommending waiting at least 4–6 months (22/77; 28.6%) or more than 6 months (20/77; 26.0%), depending on the cause of spasticity, before treating patients with ITB. This is clearly inappropriate if patients are losing range, particularly in the context of dysautonomia following brain injury, where ITB has been shown to be beneficial ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although consensus was reached that an intrathecal baclofen pump should be considered for the most severe, refractory cases, this may be unavailable in some centres. While intrathecal baclofen is well established for the treatment of severe spasticity without PSH, and case reports and series exist dating back 20 years (see reference 18 for summary), the quality of evidence remains poor for this potentially effective but invasive intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used symptomatic medications include opioids, nonselective β-blockers, α2 agonists, bromocriptine, baclofen, gabapentin, and long-acting benzodiazepines, which are primarily used to lower body temperature, control heart rate, maintain blood pressure, sedate, and relieve spasticity or decrease muscle tone. There have also been case reports on the effectiveness of intrathecal baclofen [ 29 ] and intrarectal administration [ 30 ]. A previous study also found that trazodone was effective in reducing PSH symptoms following a left temporal lobe subcortical hemorrhage in a 49-year-old woman [ 31 ].…”
Section: Clinical Management Challenges Of Pshmentioning
confidence: 99%